Children in Broken Homes: A Legal Review of Parental Responsibilities Post-Divorce - M. Nur Hilmi (al-Afkar, Journal For Islamic Studies, 2026)
The phenomenon of divorce in Indonesia shows a growing trend and has serious impacts on the psychological, social, academic, and moral conditions of children. This situation gives rise to broken homes, which place children in a vulnerable position, both emotionally and legally. This article aims to examine the legal responsibilities of parents after divorce from the perspective of positive Indonesian law and Islamic law, while analyzing their implications for child protection. This research uses a juridical-normative approach by examining Law Number 1 of 1974 concerning Marriage, the Compilation of Islamic Law (KHI), and Law Number 35 of 2014 concerning Child Protection, along with an analysis of relevant literature. The results of the study indicate that divorce does not eliminate parental responsibility for the care, education, and protection of children, as emphasized in legislation and the principle of the best interests of the child. However, the implementation of court decisions regarding child custody (hadhanah) and child support still faces legal, psychological, social, and institutional obstacles. Furthermore, child neglect is categorized as a criminal offense under national law, while in Islamic law it is considered a form of ta'zīr (indecent act) that contradicts the maqāṣid al-sharī‘ah (obligatory religious duties). Therefore, institutional reform is needed through strengthening mediation, counseling, and the establishment of specialized supervisory institutions, along with increasing public legal awareness. This way, post-divorce child protection can be more effectively implemented within a legal and social framework.